Pengaruh Latihan Kebugaran Jasmani terhadap Kesehatan dan Konsentrasi Belajar Siswa Sekolah Dasar - Rizki Bastanta B. Manalu; Gita Angelika Simbolon; Elisabet Christina Damayanti; Risos Panjaitan; Dea Florika Br Ritonga (Jurnal Pendidikan, Media, Strategi, dan Metode., 2026)
This study aims to analyze the relationship between physical fitness exercises, physical health, and learning concentration among elementary school students. The study employed a descriptive approach using simple survey data collected through a structured Google Forms questionnaire. The participants were 10 elementary school students selected through purposive sampling based on class representation and willingness to provide data with parental assistance. Data were collected through questionnaire items concerning physical activity intensity, perceived physical health, and learning concentration, and were analyzed descriptively and narratively by reading responses, grouping themes, and identifying response patterns. The findings indicate that students who regularly engaged in physical activity, particularly at least three times a week, tended to have more stable stamina, experience less fatigue, and demonstrate better learning readiness in class. In contrast, students with limited physical activity more frequently reported drowsiness, fatigue, and difficulty maintaining focus during lessons. These findings suggest that physical fitness exercises may serve as a supportive strategy for maintaining elementary students' physical health and cognitive readiness. This study recommends integrating light and structured physical activities into elementary school routines as a preventive effort to reduce learning fatigue and improve students' concentration.